Comparison of Physical Condition Profiles of Elite and Non-Elite Youth Football Players - Ahmad Nasrulloh; Sumaryanto Sumaryanto; Yudik Prasetyo; Sulistiyono Sulistiyono; Rina Yuniana (MEDIKORA, 2021)
Performance of a football player in a competitive match is influenced by good physical condition in training, competing, or in everyday life. Comprehensive ability is the hope of all football coaches. The study was conducted to determine how the comparison of the physical condition profile of youth football players in the elite and non-elite categories at the provincial level football federation, especially in SSB in the Special Region of Yogyakarta.The research method used in this research is descriptive quantitative. The subjects of this study were students or soccer athletes in elite and non-elite youth football players. The population that the researchers determined was elite and non-elite youth football players at football schools or football clubs in the DIY Province. The sampling technique was carried out by means of purposive random sampling. The instrument in this study used the MFT / Yoyo Intermitent Test, Vertical Jump Test, 30 meter Sprint Test, Illinois Test, and Sit And Reach.Based on the results of the study, it shows that the body mass index component with an average of 19.53 elite players and 19.78 non-elite players. Flexibility, elite players 34.40 and non elite players 31.14. The leg power of elite players is 45.52 and for non-elite players is 45.28. The speed component is 4.48 for elite and non-elite players, 4.95. For coordination, the elite players are 53.04 and the non-elite players are 51.20. The agility of the elite players is 18.68 and the non-elite players are 18.99. Meanwhile, the aerobic endurance for elite players was 39.85 and non-elite players were 37.97. So it can be concluded that the physical condition of soccer players which includes body mass index, flexibility, leg power, speed, coordination, agility and endurance, elite players show better results compared to non-elite players.